Acute toxicity in laboratory tests of fresh and aged residues of pesticides used in citrus on the parasitoid Aphytis melinus - Vanaclocha, Pilar; Vidal-Quist, Cristian; Oheix, S.; Montón, Helga; Planes, Laura; Catalán, José; Tena, Alejandro; Verdú, María J.; Urbaneja, Alberto (2017)
California red scale Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae) is a worldwide citrus key pest. One of the control strategies currently promoted in the Mediterranean basin is the augmentative release of the parasitoid Aphytis melinus DeBach (Hymenoptera: Aphelinidae). A clear understanding of the impact that pesticides commonly used in citrus have on this parasitoid is therefore essential to assure the efficacy of the method. The aims of this study were to evaluate the lethal effects of freshly applied and laboratory-aged residues of eighteen selected pesticides recommended in IPM for citrus on A. melinus adults. According to their toxicity on A. melinus, the pesticides could be divided in four groups. Etofenprox and chlorpyrifos were harmful and persistent; abamectin was moderately harmful and slightly persistent; dimethoate, chlorpyrifos-methyl, and spirodiclofen were slightly harmful and moderately persistent; and azadirachtin, etoxazole, fenbutaestan, hexythiazox, mancozeb, petroleum oil, pirimicarb, propargite, pymetrozine, pyriproxyfen, spirotetramat, and tebufenpyrad were considered harmless. The information presented here will help us to integrate A. melinus release within an IPM for citrus in which pesticides are still used.